A study of the relationship between neurological function and serum vitamin E concentrations in patients with cystic fibrosis. Issue 11 (November 1985) - Willison, H J; Muller, D P; Matthews, S; Jones, S; Kriss, A; Stead, R J; Hodson, M E; Harding, A E
Abstract : A patient with cystic fibrosis and undetectable serum vitamin E concentrations is described who developed a progressive spinocerebellar syndrome and pigmentary retinopathy with abnormal somatosensory and visual evoked potentials (SSEPs and VEPs). In order to assess the relationship between neurological function and serum vitamin E concentrations in cystic fibrosis, 29 unselected patients who had no neurological symptoms were examined neurologically. Ten were randomly selected for neurophysiological assessment by recording SSEPs and VEPs. Electroretinograms (ERGs) were also performed in five cases. The findings were correlated with serum vitamin E concentrations which were unknown to the neurological investigators prior to completion of the study. Only one patient had definite reflex and sensory abnormalities, and the remaining 28 were clinically normal. The ERG was abnormal in two cases, one of whom had abnormal VEPs. SSEPs were normal in all 10 cases. Twenty six patients had serum vitamin E concentrations below the normal range. In two of the three patients who had definite neurological or electrophysiological abnormalities serum vitamin E concentrations were below the median value for the whole group.